Death by tiara - Levine, Laura, 1943- (Levine, Laura, 1943- Jaine Austen mystery., 2015)
When she is hired to write lyrics for a contestant in the talent competition for the Miss Teen Queen America pageant, freelance writer Jaine Austen is plunged into a glittering nightmare of vicious stage moms, exacting judges and trash-talking teens after a catfight turns deadly.